Cyclic Bayesian Network – Markov Process Approach - Kłopotek, Mieczysław (Studia Informatica. System and information technology, 2006)
The paper proposes a new interpretation of the concept of cyclic Bayesian Networks, based on stationary Markov processes over feature vector state transitions.